Ultrasound-targeted microbubble destruction promotes PDGF-primed bone mesenchymal stem cell transplantation for myocardial protection in acute Myocardial Infarction in rats - Zhenxing Sun; Yu Cai; Yihan Chen; Qiaofeng Jin; Ziming Zhang; Li Zhang; Yuman Li; Lei Huang; Jing Wang; Yali Yang; Qing Lv; Zhengyang Han; et al. (Journal of Nanobiotechnology, 2023)
Abstract Background Ultrasound-targeted microbubble destruction (UTMD) has emerged as a promising strategy for the targeted delivery of bone marrow mesenchymal stem cells (MSCs) to the ischemic myocardium. However, the limited migration capacity and poor survival of MSCs remains a major therapeutic barrier. The present study was performed to investigate the synergistic effect of UTMD with platelet-derived growth factor BB (PDGF-BB) on the homing of MSCs for acute myocardial infarction (AMI). Methods MSCs from male donor rats were treated with PDGF-BB, and a novel microbubble formulation was prepared using a thin-film hydration method. In vivo, MSCs with or without PDGF-BB pretreatment were transplanted by UTMD after inducing AMI in experimental rats. The therapeutic efficacy of PDGF-BB-primed MSCs on myocardial apoptosis, angiogenesis, cardiac function and scar repair was estimated. The effects and molecular mechanisms of PDGF-BB on MSC migration and survival were explored in vitro. Results The results showed that the biological effects of UTMD increased the local levels of stromal-derived factor-1 (SDF-1), which promoted the migration of transplanted MSCs to the ischemic region. Compared with UTMD alone, UTMD combined with PDGF-BB pretreatment significantly increased the cardiac homing of MSCs, which subsequently reduced myocardial apoptosis, promoted neovascularization and tissue repair, and increased cardiac function 30 days after MI. The vitro results demonstrated that PDGF-BB enhanced MSC migration and protected these cells from H2O2-induced apoptosis. Mechanistically, PDGF-BB pretreatment promoted MSC migration and inhibited H2O2-induced MSC apoptosis via activation of the phosphatidylinositol 3-kinase/serine-threonine kinase (PI3K/Akt) pathway. Furthermore, crosstalk between PDGF-BB and stromal-derived factor-1/chemokine receptor 4 (SDF-1/CXCR4) is involved in the PI3K/AKT signaling pathway. Conclusion The present study demonstrated that UTMD combined with PDGF-BB treatment could enhance the homing ability of MSCs, thus alleviating AMI in rats. Therefore, UTMD combined with PDGF-BB pretreatment may offer exciting therapeutic opportunities for strengthening MSC therapy in ischemic diseases.